2006
DOI: 10.1897/05-519r.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of polar fractions from a herbicide‐contaminated soil does not correspond to parent contaminants

Abstract: Fractionation with biological and chemical analysis has been proposed to characterize the risk associated with complex samples. Thus, we have employed hot pressurized water for fractionating a herbicide-contaminated soil. Genotoxicity was found in polar and midpolarity fractions extracted from a historically herbicide-contaminated soil. However, the parent herbicides as well as organic solvent extracts (consisting of herbicides) were not genotoxic. Thus, polar organics formed by natural degradation of herbicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Such a hypothesis can be supported by the presence of microorganisms that were shown to have important roles in allelopathy; they have the potential to modify pollutant effects . It was also observed that genotoxicity of herbicide fractions from soil did not correlate with parent contaminants and organic matter of soil was shown to change triketone features probably as a result of the presence of humic acids …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a hypothesis can be supported by the presence of microorganisms that were shown to have important roles in allelopathy; they have the potential to modify pollutant effects . It was also observed that genotoxicity of herbicide fractions from soil did not correlate with parent contaminants and organic matter of soil was shown to change triketone features probably as a result of the presence of humic acids …”
Section: Results and Discussionmentioning
confidence: 99%
“…Such a hypothesis can be supported by the presence of microorganisms that were shown to have important roles in allelopathy; they have the potential to modify pollutant effects. 32 It was also observed that genotoxicity of herbicide fractions from soil did not correlate with parent contaminants 33 and organic matter of soil was shown to change triketone features probably as a result of the presence of humic acids. 34 We have shown that a pesticide, sulcotrione, can be harmful for health and the environment and then transformed by photolysis into a product that was toxic but had lost the specific herbicide toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%